Challenging perspectives: narrative approaches in Ulrike Almut Sandig's Flamingos. Geschichten - Bartel, Heike (Taylor & Francis, 2018)
In Flamingos, Ulrike Almut Sandig’s collection of eleven stories, narrative perspective comes under constant challenge so that these superficially simple texts reveal on closer inspection a multi-layered complexity. The following close readings of a selection of stories will outline how intimately Sandig’s narrative approach links form and content. The stories focus on the solitary or ‘odd’ individual, on gaps or missing pieces in the sequence of events, on the Fluchtpunkte or vanishing points that the seemingly limited narrative perspective in each story leads to. The stories with their detached tone and understated manner are about an unstable, uncentred world. Cumulatively these views from the margins build up a bigger picture, a mosaic composed from otherwise only loosely connected pieces. Whilst Sandig’s texts challenge the reader through their complex handling of the narrative perspective, they also query through their innovative form the authority of particular ways of viewing and ordering the world both ideologically and aesthetically.